2015
DOI: 10.1002/mame.201500250
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy of Polymers: The Role of Specific Reactions in the Condensed Phase

Abstract: Condensed-phase mechanisms play a major role in fire-retardant polymers. Generations of development have followed the concept of charring to improve fire properties. W1hereas the principal reactions are believed to be known, the specific description for multicomponent systems is lacking, as is the picture across different systems. A two-step approach is proposed in general, and also presented in greater detail. The second step covers the specific reactions controlling charring, whereas the actual reactants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(119 citation statements)
references
References 72 publications
2
115
0
Order By: Relevance
“…[31] Recently, J. Artner et al synthesized DOPO-based diaminic hardener for DGEBA/DDS carbon fiber reinforced composites. [34] Since P-FRs has been regarded as very promising and effective non-halogenated flame retardant for polymers, in particular for epoxy resin, further understanding about the impact of phosphorus's chemical surrounding of P-FRs on the flame-retardant efficiency is very important to the development of high efficiency of flame retardant for epoxy resin. [12] Z. Li et al found a good synergistic effect between polyhedral oligomeric octadiphenylsulfonylsilsesquioxane (ODPSS) and DOPO on flameretardant epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Recently, J. Artner et al synthesized DOPO-based diaminic hardener for DGEBA/DDS carbon fiber reinforced composites. [34] Since P-FRs has been regarded as very promising and effective non-halogenated flame retardant for polymers, in particular for epoxy resin, further understanding about the impact of phosphorus's chemical surrounding of P-FRs on the flame-retardant efficiency is very important to the development of high efficiency of flame retardant for epoxy resin. [12] Z. Li et al found a good synergistic effect between polyhedral oligomeric octadiphenylsulfonylsilsesquioxane (ODPSS) and DOPO on flameretardant epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…When the temperature is above 500 8C, several new absorption peaks are detected in the spectra of residual chars for EP/DAP10 and EP/AP10, apart from the peak at 1594 cm 21 due to the absorption of polyaromatic structures. As to EP/ DAP10, the peak at 1096 cm 21 belongs to the stretching vibration of PAOAC Ar bond, 35,43 and peaks at 983 and 500 cm 21 are attributed to the stretching vibration of PAOAP bond and the bending vibration of OAPAO bond, respectively. 44 For EP/ AP10, the absorptions at 1092, 980, and 510 cm 21 assigned to PAOAC Ar , PAOAP, and OAPAO bonds, respectively, are also observed in the spectrum.…”
mentioning
confidence: 98%
“…33,36 In the case of AP, the absorptions at 3000 to 2800 cm 21 in the spectrum at 25 8C are assigned to the stretching vibrations of ACH 3 and ACH 2 A groups, and several peaks at 1198 cm 21 (P@O), 1052, 1022 cm 21 (PAOAC), and 979 cm 21 (PAO) are also identified. At 300 8C, it is obvious that the absorptions due to 35,37 This can be regarded as an indirect sign that ethanol is generated and released into the gas phase during the early degradation of AP. In the meantime, new absorption peaks at 1635, 1224, 1140, 1085, 1067, and 526 cm 21 due to the characteristic absorptions of O@PAOH group are detected, which indicates the formation of phosphoric acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12B-F). The compact char layers can effectively protect the internal structures, inhibit the heat transmission and reduce the fuel gases when the fire in contact with them [53][54][55]. However, when the mass fraction of HP-1001-COOH exceeds 30 wt.%, many holes on the surface of residues were observed, due to the further decrease of the crosslinking density and looser network of the cured epoxy resin.…”
Section: Morphology Of the Residues From Cone Calorimeter Testmentioning
confidence: 91%